2000
DOI: 10.1002/1521-396x(200003)178:1<r1::aid-pssa99991>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Small Polarons in Reduced Iron-Doped Lithium-Niobate Crystals by Non-Steady-State Photocurrent Techniques

Abstract: Photorefractive iron-doped lithium-niobate crystals (LiNbO 3 : Fe) are of special interest for applications in the fields of optical communication techniques and holographic data storage. Recently, considerable attention has been concentrated on a shallow photorefractive center in LiNbO 3 : Fe, which enables non-volatile storage of holograms by two-color processes [1 to 4]. This center is attributed to the intrinsic Nb 4a5 Li antisite defect (Nb 4a5 on Li site) [5,6]. The center with a trapped electron (Nb 4 L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…Furthermore, the activation energy for migration of small polarons is around 0.3 eV, Peithmann et al (2000) clearly much lower than what was observed here.…”
Section: Discussioncontrasting
confidence: 73%
“…Furthermore, the activation energy for migration of small polarons is around 0.3 eV, Peithmann et al (2000) clearly much lower than what was observed here.…”
Section: Discussioncontrasting
confidence: 73%
“…Most recent results concerns the realization of photorefractive optical waveguides in Fe:LN by ion implantation [14]. Using these configurations, the first demonstrators of optical interconnections integrated optical circuits and sensors with a holographic stage have been already reported [15][16][17][18][19][20]. The main limitation of these optical processing schemes is that their full potential is nowadays difficult to miniaturize and integrate in a http://dx.doi.org/10.1016/j.optmat.2014.05.020 0925-3467/Ó 2014 Elsevier B.V. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%